IMPLEMENTATION OF CHILD-FRIENDLY REGENCY POLICY AT THE OFFICE OF SOCIAL AFFAIRS, WOMEN’S EMPOWERMENT, CHILD PROTECTION, AND FAMILY PLANNING IN LANDAK REGENCY - Grace Kurnianti; Yulius Yohanes; Arifin (CV. Radja Publika, 2026)
This thesis aims to analyze the implementation of child-friendly policies at the Social Services, Women's Empowerment, Child Protection, and Family Planning Office of Landak Regency. The problem in this study is that it still faces obstacles in cross-sector coordination that is not optimal. The lack of intensive socialization causes some stakeholders to only understand the policy administratively without embracing the principles of fulfilling children's rights. The purpose of this study is to describe and analyze the process of implementing child-friendly policies at the Social Services, Women's Empowerment, Child Protection, and Family Planning Office of Landak Regency, seen from the aspects of organization, interpretation, and application. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The results of the study indicate that the implementation of the Child-Friendly Child Protection (KLA) policy in Landak Regency at the organizational stage, institutional structure and division of tasks have been formed and are running according to regulations. However, there are still obstacles such as limited resources. At the interpretation stage, socialization and counseling efforts regarding the KLA policy have been carried out to the community, but understanding of the policy is not yet evenly distributed. Meanwhile, at the application or implementation stage, various programs and activities related to the fulfillment of children's rights and protection have been implemented, but their implementation in the field has not been optimal. This research recommends strengthening cross-sector coordination, increasing human resource capacity, and optimizing community outreach and participation to ensure more effective implementation of the Child-Friendly Childcare (KLA) policy in fulfilling and protecting children's rights in Landak Regency.